Discovery of potent aryl-substituted 3-[(3-methylpyridine-2-carbonyl) amino]-2, 4-dimethyl-benzoic acid EP4 antagonists with improved pharmacokinetic profile. Issue 3 (1st February 2016) - Blanco, Maria-Jesus; Vetman, Tatiana; Chandrasekhar, Srinivasan; Fisher, Matthew J.; Harvey, Anita; Chambers, Mark; Lin, Chaohua; Mudra, Daniel; Oskins, Jennifer; Wang, Xu-Shan; Yu, Xiao-Peng; Warshawsky, Alan M.
Graphical abstract: Abstract: Two new series of EP4 antagonists containing a 3-methylaryl-2-carbonyl core have been identified. One series has a 3-substituted-phenyl core, while the other one incorporates a 3-substituted pyridine. Both series led to compounds with potent activity in functional and human whole blood (hWB) assays. In the pyridine series, compound7a was found to be a highly potent and selective EP4 antagonist, with suitable rat and dog pharmacokinetic profiles.